BTN1A1 is a novel immune checkpoint mutually exclusive to PD-L1 - Young-Seung Kim; Bong-Ki Hong; Steven H Lin; Seung-Hoon Lee; Stephen S Yoo; Chunai Wu; Andrew H Park; Hyunjin Jung (Journal for ImmunoTherapy of Cancer)
Background While Programmed cell death protein 1 (PD-1)/programmed cell death-ligand 1 (PD-L1) blockade is a potent antitumor treatment strategy, it is effective in only limited subsets of patients with cancer, emphasizing the need for the identification of additional immune checkpoints. Butyrophilin 1A1 (BTN1A1) has been reported to exhibit potential immunoregulatory activity, but its ability to function as an immune checkpoint remains to be systematically assessed, and the mechanisms underlying such activity have yet to be characterized.Methods BTN1A1 expression was evaluated in primary tumor tissue samples, and its ability to suppress T-cell activation and T cell-dependent tumor clearance was examined. The relationship between BTN1A1 and PD-L1 expression was further characterized, followed by the development of a BTN1A1-specific antibody that was administered to tumor-bearing mice to test the amenability of this target to immune checkpoint inhibition.Results BTN1A1 was confirmed to suppress T-cell activation in vitro and in vivo. Robust BTN1A1 expression was detected in a range of solid tumor tissue samples, and BTN1A1 expression was mutually exclusive with that of PD-L1 as a consequence of its inhibition of Janus-activated kinase/signal transducer and activator of transcription signaling-induced PD-L1 upregulation. Antibody-mediated BTN1A1 blockade suppressed tumor growth and enhanced immune cell infiltration in syngeneic tumor-bearing mice.Conclusion Together, these results confirm that the potential of BTN1A1 is a bona fide immune checkpoint and a viable immunotherapeutic target for the treatment of individuals with anti-PD-1/PD-L1 refractory or resistant disease, opening new avenues to improving survival outcomes for patients with a range of cancers.